FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI, STRESS KERJA SEBAGAI MEDIASI - Muadi, 1252020021; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of the study is to analyze and describe the influence of role conflict , role ambiguity to job stress . In addition, to analyze and describe the influence of role conflict , role ambiguity and job stress on employee performance of  the Secretary of  Pekalongan City. This study also aims at whether job stress mediates the effect of role conflict and role ambiguity on employee performance . The population used in this study were employees on  the Secretary of  Pekalongan City. While the sample used in this study were 121. The analytical tool used in this study using a testing instrument, testing and regression testing linear models . The results of this study it can be concluded that (1) the role of conflict positive effect on job stress . (2) The ambiguity of the role of a positive effect on job stress. (3) role conflict negatively affect employee performance. (4) The ambiguity of the role of negative influence on employee performance. (5) Work stress negatively affect employee performance. (6) Job stress does not mediate the effect of role conflict on employee performance. (7) Job stress does not mediate the effect of role ambiguity on employee performance Keywords: role conflict, role ambiguity, job stress and performance